The perception of effort, training load, and exercise performance in the heat - Borg, D. N. (Queensland University of Technology, 2019)
The thesis examined the influence of environmental forecast on the perception of effort during cycling in the heat; and the effects of daily cold-and hot-water recovery use during heat acclimation training on training load tolerance, and 20 km cycling performance in the heat. The thesis findings suggest that environmental temperature awareness my not affect the perception of effort during cycling in the heat; and the use of thermal recoveries during heat acclimation training, irrespective of water temperature, may impair training tolerance, but have little effect on post-intervention 20 km cycling performance in the heat compared to no water immersion recovery.